Coding Strip: A Pedagogical Tool for Teaching and Learning Programming Concepts through Comics - Suh, Sangho; Lee, Martinet; Xia, Gracie; law, Edith (Proceedings (IEEE Symposium on Visual Languages and Human-Centric Computing), 2020)
The abstract nature of programming makes learning to code a daunting undertaking for many novice learners. In this work, we advocate the use of comics-a medium capable of presenting abstract ideas in a concrete, familiar way-for introducing programming concepts. Particularly, we propose a design process and related tools to help students and teachers create coding strips, a form of comic strips that are associated with a piece of code. We conducted two design workshops with students and high school computer science teachers to evaluate our design process and tools. We find that our design process and tools are effective at supporting the design of coding strips and that both students and teachers are excited about using coding strip as a tool for learning and teaching programming concepts.